Breast Feeding among Mothers Attending Immunization Clinic at Health Centresin Rivers State Nigeria: An Institutional-based Survey - , Nneka Gabriel-Job; , Uju S. Azubogu (Archives of Current Research International, 2020)
Introduction: Breastfeeding, especially exclusive breastfeeding (EBF), is considered effective for children’s survival. The practice and duration of EBF still remain low. The aim of this study was to determine the pattern of breastfeeding and factors preventing EBF practicesamong mothers attending Health Centres for immunization services in Rivers State, Nigeria. Methodology: Participants (n=480) were mothers who delivered their babies 4-18 months before onset of the study and attended immunization clinic (Health Centres in Obio/Akpor, Rivers State, Nigeria). An interviewer administered pre-tested, semi structured questionnaire was used to obtain the following information: their knowledge of EBF, their breast feeding practices, and reasons for not practicing EBF. Results: Majority (86.3%) had heard of EBF, having heard it from a health facility. Only 153 (32.0%) women agreed that colostrum should be fed to a new born. 338 (70.4%) responded that the duration of EBF is 6 months while 302 (62.1%) responded that breast feeding should be stopped immediately after the infant becomes one year old. 149 (31.0%) practiced EBF; EBF was significantly related to antenatal care attendance(p = 0.02),spousal support(p = 0.03) and parity (p = 0.003). Returning to work after childbirth was the main reason for not practicing EBF. Conclusion: Adequate information on the benefits and duration of breastfeeding is needed to enable effective breastfeeding. Support from the family and work place may enhance the practice of EBF in Rivers State.